Effects of exogenous 2,4-epibrassinolide on antioxidant enzyme activities of camphor seedlings under salt stress - WANG Shutian; WANG Jinping; ZHANG Jinchi; YUE Jianmin (浙江大学学报. 农业与生命科学版)
Cinnamomum camphora, also known as camphor tree, is a kind of excellent tree for afforestation, street and shade, which is of great use to water conservation, making environment green and beauty. Cinnamomum camphora prefers warm and humid climate, and has strong taproot, deep- rootedness and strong sprouting ability, which is of considerable application value in southern coastal areas of China. However, camphor is intolerant to drought, barren and saline soil, and its requirement for soil salinity should be within 0.2%. Camphor grows well in acid yellow soil, but is susceptible to yellow leaf disease in alkaline soil. Moreover, some other elements such as low temperature, weak light and soil secondary salt damage of high concentration would lead to growth failure, fertility inhibition, and even death of camphor. In coastal areas of Jiangsu Province, high soil pH and low organic matter content are not beneficial to the growth and development of camphor, which seriously affect the greening cultivation, introduction and popularization. Therefore, it is of great significance to study the mechanism of salinity tolerance of C. camphora.In this study, two application methods (soaking seed, soaking seed and spraying leaf) of 2,4-epibrassinolide (EBR) were designed to reveal the effect of EBR on the salt-tolerance of C. camphora. Different concentrations of EBR (0.1, 0.2, 0.3, 0.4, 0.5 mg/L) were used for soaking seeds and spraying leaf under a steadfast salt concentration at 4‰, respectively; meanwhile, distilled water treatment (CK1) and distilled water + 4‰ salt treatment (CK2) were used as controls. Then soluble sugar, soluble protein, malondialdehyde (MDA) contents and antioxidant enzyme activities were analyzed to reveal the variation characteristics of C. camphora under the salt stress.The result showed that: under the 4‰ salt stress, the external application of EBR (soaking seed and spraying leaf) could decrease MDA content, and when the concentration of EBR was 0.4 mg/L, MDA content reached the minimum. Additionally, soaking seed treatment with EBR could increase the contents of soluble protein and soluble sugar. Compared with the CK2, when the concentration of EBR (soaking seed) was 0.5 mg/L, soluble protein content increased by 31.80% with significant difference; when the concentration of EBR (soaking seed and spraying leaf) was 0.5 mg/L, soluble sugar content significantly increased by 24.80%. Compared with the CK1, the superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT) activities of camphor seedlings under the CK2 increased by 21.48%, 13.30% and 8.65%, respectively. Moreover, 0.5 mg/L EBR applied by soaking seed, soaking seed and spraying leaf had the best effect to improve SOD content under the 4‰ salt stress, which was significantly improved by 49.49% and 55.11% (P< 0.05), respectively. Under the same condition, the activities of SOD and POD showed a fluctuating upward trend with the increase of EBR concentration, but the difference was not significant; however, the activity of CAT increased first and then decreased under the treatment of soaking seed and spraying leaf, and 0.4 mg/L EBR had the best effect. Above all, the variation trend of SOD, POD and CAT activities was basically the same under various conditions, which indicates that their mutual cooperation can alleviate the damage of reactive oxygen species caused by salt stress. Among the three antioxidant enzymes, SOD activity changed most remarkably, and POD was second, but CAT changed least, indicating SOD has a relatively greater impact on antioxidant enzyme system.In summary, under the salt stress, a certain concentration of EBR can improve antioxidant status, scavenge reactive oxygen species and membrane stability, and enhance salt resistance of camphor seedlings. Moreover, the method of soaking seed and spraying leaf has better effect than soaking seed.